Ethnoconservation of Jugo Villagers in Ngunggahne Beras Tradition - Tutut Indah Sulistiyowati; Farida Nurlaila Zunaidah; Poppy Rahmatika Primandiri (Journal of Tropical Ethnobiology, 2023)
Ngunggahne Beras is a respect to Dewi Sri as the keeper and fortune giver for farmers. The people of Jugo Village preserve the tradition well. Uborampen prepared by the villagers in the Ngunggahne Beras tradition is different from other villages. The uborampen consists of various plants that are sublime symbols and offering to God. This study is conducted using an ethnographic approach through an in-depth interview with performers of tradition and traditional figures. The interview results show that all plants used in the tradition are obtained from Jugo Village. The plants mostly planted are rose (74%), jasmine (62%), and rice (61%). Plants obtained from other areas include pandan mendong (99%), pinang (betel palm) (96%), and coconut (96%). Therefore, the Ngunggahne Beras tradition is the application of ethnoconservation conducted by the Jugo villagers. Through tradition, the villagers have conserved rose flower (Rosa sp), jasmine (Jasminum sp), white champaca (Michelia alba), cananga (Cananga sp), latundan banana (Musa acuminata), coconut (Cocos nucifera), betel leaf (Piper betle L), dadap serep (Erythrina subumbrans), betel nut (Areca catechu), kebak (Macaranga sp) leaves, pandan mendong (Fimbristylis umbellaris), and rice (Oryza sativa).